Variable energy X-ray fluorescence source. (1st January 2023) - Elliott, S.R.; Bond, E.M.; Dodson, B.; Rusev, G.; Massarczyk, R.; Meijer, S.J.; Stortini, M.; Wiseman, C.
Abstract: We detail the design of a variable energy, x-ray fluorescence source using a low activity (1.8×10 6 dpm) 99 Tc β source that irradiates thin foils. By rotating the source among foils of Ti, Zn, Nb, Ag, and Au, the device produces x rays between 4 and 70 keV at a rate near 1 Hz. When the source is placed in a storage position, the external radiation is non-detectable. The design of the shielding and rotation mechanism permits use in vacuum and at liquid nitrogen temperature. The design is intended for the study of the low energy response to radiation impinging upon Ge detector surfaces. The source will be useful for understanding the detector response in large-scale Ge arrays such as Majorana and LEGEND.